Prioritizing Extension Resources Using Perceived Importance and Satisfaction: An Underutilized Approach - Laura A. Warner; Anil Kumar Chaudhary (EDIS)
Importance-performance analysis, or IPA, measure how people feel about certain characteristics of a place, issue, or program. Extension professionals can use IPA to make decisions and prioritize resources by understanding how clients rate the importance of and satisfaction with specific attributes of a program or facility. This three-page fact sheet explains IPA and how to use it. It is the first article in the Importance-performance Analysis series, a series of three on using IPA to prioritize Extension resources. Written by Laura A. Warner and Anil Jumar Chaudhary, and published by the Department of Agricultural Education and Communication, May 2016.